Ibuprofen salt production and its application in tablet dosage form - Hadisoewignyo, Lannie; Fudholi, Achmad; Muchalal, M. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
Ibuprofen is an anti-inflammatory drug and is practically insoluble in water. The low melting point and the poor flowability of ibuprofen can lead to process difficulty in tablets production. The purpose of this research was to make the sodium salt form of ibuprofen which has better solubility in water.Sodium ibuprofen salt was prepared by reacting the ibuprofen and sodium hydroxide, then characterized using TG/DTA, DSC, spectrophotometer UV-VIS, spectrophotometer IR, X-ray diffraction, and SEM. Tablets were prepared by wet granulation method.The characterization result showed that sodium ibuprofen result of the synthesis was dehydrate form with melting point of 199.9 °C. Granules of sodium ibuprofen result of the synthesis had better flowability and bigger density than ibuprofen granules. The physical characterization of the tablet showed that the formula of sodium ibuprofen resulted from the. Sodium ibuprofen showed the higher release rate than ibuprofen so can give quicker onset of action.Key words: sodium ibuprofen, ibuprofen, dissolution.